2019
DOI: 10.14254/1800-5845/2019.15-1.8
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Organizational Culture and Dimensions on Job Satisfaction and Work-Life Balance

Abstract: The purpose of this paper is to analyze the moderating effects of organizational culture and organizational culture dimensions on the relationship between job satisfaction and work-life balance. The research also analyses the differences in the perception of organizational culture and its dimensions between managers and nonmanagement employees in the wood product manufacturing industry. Methodology: The research was administered to 200 employees from five wood product manufacturing companies. Data was collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The effect of job satisfaction on subjective well-being can be not just direct one, there is a lot of intermediaries, like gender or religious perception of the life quality (Bilan et al, 2019), attitude to the trust (Lazányi & Bilan, 2017), the hours worked vs salaries earned in teh contest of the intertemporal labour substitution (Šabić-Lipovača etc, 2016), organizational culture and organizational culture dimensions (Stefanovska-Petkovska etc, 2019), the managing or non-managing position (Stefanovska-Petkovska et al, 2019;Bratu & Cioca, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The effect of job satisfaction on subjective well-being can be not just direct one, there is a lot of intermediaries, like gender or religious perception of the life quality (Bilan et al, 2019), attitude to the trust (Lazányi & Bilan, 2017), the hours worked vs salaries earned in teh contest of the intertemporal labour substitution (Šabić-Lipovača etc, 2016), organizational culture and organizational culture dimensions (Stefanovska-Petkovska etc, 2019), the managing or non-managing position (Stefanovska-Petkovska et al, 2019;Bratu & Cioca, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Employees with a good work-life balance can manage time for family and work by using flexible working hours, which is one of the factors that can affect job satisfaction. This is supported by Saad and Sumaiti (2010); Wenno (2018); Stefanovska-Petkovska et al (2019) which states that a good work-life balance can improve employee job satisfaction.…”
Section: Resultsmentioning
confidence: 82%
“…That research shows that work-life balance, where employees appreciated and recognized, can increase job satisfaction. Stefanovska et al (2019) in research on the variables of work-life balance and job satisfaction conducted in manufacturing companies shows that work-life balance has a positive impact on job satisfaction. In line with that, it is suggested that the manager's behavior towards employees also determines the support or obstacles in the company.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking the discussion further, while organizational culture research has gained traction, past scholars have opinionated that a positive organizational culture can maintain work-life balance and work flexibility (Eversole et al, 2012;Stefanovska-Petkovska et al, 2019). Similarly, past studies have reported that positive organizational culture can play a critical role in bringing drastic behavioural changes in the employees .…”
Section: Barriers To the Hybrid Work Modelmentioning
confidence: 99%